ANALISIS KESALAHAN TULISAN SISWA KELAS VIII PP. RAUDHATUS SALAAM PADA MATA PELAJARAN IMLA: ANALYSIS OF WRITING ERRORS OF GRADE 8 STUDENTS OF RAUDHATUS SALAAM ISLAMIC BOARDING SCHOOL IN THE SUBJECT IMLA' - Hania Qisty; Ahmad Miftahuddin (Universitas Negeri Semarang, 2025)
Arabic language learning, especially Imla skills, is an important focus in countries with large Muslim populations. Imla refers to the ability to write correctly according to the rules of Arabic orthography and grammar. This research aims to identify and analyze IMLA writing errors that are often made by class VIII students at PP. Raudhatus Salaam in the 2024-2025 academic year. The research method used is a qualitative approach with a descriptive design, involving observation, interviews and analysis of student written documentation. The research results showed that students experienced various types of errors in writing Imla, including errors in writing harakat (15%), letters with similar sounds (21%), long and short sounds (24%), and errors in connecting or separating words (21%). This error is caused by several factors, such as a lack of understanding of vocabulary, unclear pronunciation, and less effective learning methods. In-depth analysis revealed that lack of regular writing practice was the main cause of errors, with 48% of the total causal factors identified. This research also found that improvement efforts such as regular Imla writing practice and increased pronunciation practice can help improve students' writing skills. By providing practical recommendations for educators, it is hoped that this research can contribute to the development of more effective learning strategies to improve Arabic writing skills among students. These findings emphasize the importance of a deep understanding of Arabic writing rules in order to reduce errors in IMLA and improve the overall quality of Arabic language learning.